Caenorhabditis elegans-based analysis of Salmonella enterica - Khoo, Chai Hoon; Sim, Jiun Horng; Mohd Sidik, Shiran; Radu, Son; Sukardi, Sabrina; Awang Salleh, Noorzaleha; Lee, Learn Han; Cheah, Yoke Kqueen (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Caenorhabditis elegans (C. elegans) have been widely used as an infection model for mammalian related pathogens with promising results. The bacterial factors required for virulence in non-mammalian host C. elegans play a role in mammalian systems. Previous reported that Salmonella found in vegetable and poultry meat could be potential health hazards to human. This study evaluated the pathogenicity of various serovars of Salmonella enterica (S. enterica) that recovered from local indigenous vegetables and poultry meat using C. elegans as a simple host model. Almost all S. enterica isolates were capable of colonizing the intestine of C. elegans, causing a significant reduction in the survival of nematodes. The colonization of Salmonella in C. elegans revealed that the ability of S. enterica in killing C. elegans correlates with its accumulation in the intestine to achieve full pathogenicity. Using this model, the virulence mechanisms of opportunistic pathogenic S. enterica were found to be not only relevant for the interactions of the bacteria with C. elegans but also with mammalian hosts including humans. Hence, C. elegans model could provide valuable insight into preliminary factors from the host that contributes to the environmental bacterial pathogenesis scenario.